The effect of product diversity and service quality on loyalty with customer satisfaction as an intervening variable (Study of Toko Pertanian Subur, Pace Nganjuk District) - Nasikhak, Niamin Nurin; Firmansyah, Fani (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2021)
Customer orientation is one of the solutions to overcome competition between businesses in this era. As many similar businesses have emerged, generating customer loyalty is one of the company’s strategies to compete and increase the sales of products. The objective of this study is to determine the effect of product diversity and quality of service on loyalty in terms of customer satisfaction. The quantitative approach is chosen in this study to obtain the expected results, while the path analysis test and the classical assumption test are used as the analysis model. The data source referred to in this study is the result of a questionnaire in the form of respondents’ responses. The population in this study were all customers of the “Toko Pertanian Subur”. A total of 98 respondents were taken as the sample which was determined by purposive sampling technique. After conducting the research, it is found that product diversity and service quality had a positive effect directly on customer loyalty with a significance level of less than alpha (0.050). The product diversity variable also does not have a mediating effect on loyalty when viewed from customer satisfaction. In addition, there is no mediating effect between service quality variables on loyalty in terms of customer satisfaction.